Electronic Green Journal (EGJ) - William T. Johnson (Issues in Science and Technology Librarianship)
The challenge of finding quality information on environmental topics has become quite problematic as the dawn of the new millennium approaches. Information overload threatens to undermine educational resource utilization of electronic and print media. Though information overload is not a new problem, the need for hassle-free, full-text, quality information on environmental topics is especially relevant today. In light of this situation, the mission of Electronic Green Journal (EGJ) is to provide a well organized source of scholarly articles on international environmental issues. EGJ is particularly well suited to students conducting research on a wide variety of environmental topics.